A review of barriers and benefits for implementing computational thinking initiatives in secondary schools - Ahamad Said, Nur Nadhirah; Hanafi, Hafizul Fahri; Naning, Fatin Hana; Mat Alim, Muliyati; Ika Parma Dewi (Journal of ICT in Education, 2024)
Computational thinking (CT) has become an essential skill for students to develop in preparation for an increasingly digital world. CT is widely recognized as a fundamental literacy important for student success across disciplines. However, significant barriers exist to integrating CT initiatives in secondary grades due to packed curricula, assessments, lack of teacher preparation, and the perception of CT as an isolated skill. This narrative review aims to analyse secondary schools’ major obstacles and the significant advantages they can attain in instituting computational thinking programs. A narrative analysis of recent literature synthesizes the two key themes, namely the barriers and benefits related to secondary CT integration to elucidate the necessary trade-offs, priorities, and costs to provide well-informed, equitable recommendations for implementing solutions. In summary, while the integration of CT in secondary schools is imperative for equipping students with future-ready skills, it requires addressing teacher misconceptions and structural barriers. Properly prioritized, CT literacy has the potential to revolutionize secondary education pedagogy and empower students to become proactive creators of technology.